QSAR study of flavonoids as platelet-activating factor (PAF) receptor binding antagonists - Abdullah, Nor Hayati; Kiong, Ling Sui; Noorbatcha, Ibrahim Ali (AENSI Publications, 2014)
Flavonoids are natural inhibitors against platelet activating factor (PAF) receptor. PAF is involved in several patho-physiological conditions such as inflammation, atherosclerosis, asthma and thrombosis. The PAF actions can be inhibited by blocking its receptor with an antagonist. The aim of this study was to find the structure activity relationship between the PAF receptor binding antagonist activity and the structure based properties of flavonoids 1-11 by using quantum chemical quantitative structure activity relationship (QSAR) approach. The semi-empirical quantum chemical method was used to optimize the molecular structures of the flavanoids and various quantum chemical descriptors were calculated from the optimized structures. Heuristic and multi-linear regression methods were used to determine the correlation between the quantum chemical properties and the experimental PAF receptor binding inhibitory activity. The best correlation equation was obtained using multi-linear correlation method with three descriptors and correlation coefficient, R2= 0.9632